Natural and human-induced Holocene paleoenvironmental changes on the Guadiana shelf (northern Gulf of Cadiz) - Mendes, Isabel (2017)
Three contrasting sedimentary environments on the continental shelf off the Guadiana River (northern Gulf of Cadiz) were integrated in a chronological framework and analysed in terms of sedimentology and benthic foraminiferal assemblages to understand the Holocene paleoenvironmental evolution. The analysed environments differ in terms of their depositional regimes and benthic foraminiferal assemblages. However, a dominant fluvial origin of the sand fraction was observed in all three environments. Holocene sedimentary processes were mainly controlled by natural (sea level changes and climate variations) and human-induced processes (e.g. deforestation, agriculture) along four evolutionary stages. The three older stages were mainly influenced by natural processes, such as sea level variations and fluvial inputs, whereas the most recent stage reflects a combination of climatic- and human-induced processes. A deepening of sedimentary environments related to a period of rapid sea level rise, strongly influenced by river discharges occurred from c. 11,500 to c. 10,000 cal. yr BP. A reduction in sediment export to the shelf, as a result of the continuous and rapid sea level rise and enhanced estuary infilling reflects the second stage, from c. 10,000 to c. 5000 cal. yr BP. The beginning of the third stage, from c. 5000 to c. 1500–1000 cal. yr BP, is marked by a sea-level slowdown and the relatively stable climate and environmental conditions. The fourth stage, from c. 1500–1000 cal. yr BP to Recent times, reflects the intensification of human-induced processes and climatic variability in the Guadiana River basin. This stage also reflects modern depositional conditions, with the formation of a proximal prodeltaic wedge and a distal muddy body.